Ignition : (Island Press, 2007)
The evidence is irrefutable: global warming is real. While the debate continues about just how much damage spiking temperatures will wreak, we know the threat to our homes, health, and even way of life is dire. So why isn’t America doing anything? Where is the national campaign to stop this catastrophe?